2000
DOI: 10.1073/pnas.080079097
|View full text |Cite
|
Sign up to set email alerts
|

Single-electron reduction of the oxidized state is coupled to proton uptake via the K pathway in Paracoccus denitrificans cytochrome c oxidase

Abstract: The reductive part of the catalytic cycle of cytochrome c oxidase from Paracoccus denitrificans was examined by using time-resolved potential measurements on black lipid membranes. Proteoliposomes were adsorbed to the black lipid membranes and Ru II (2,2-bipyridyl)3 2؉ was used as photoreductant to measure flash-induced membrane potential generation. Single-electron reduction of the oxidized wild-type cytochrome c oxidase reveals two phases of membrane potential generation (1 Ϸ 20 s and 2 Ϸ 175 s) at pH 7.4. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 33 publications
7
80
0
Order By: Relevance
“…There is evidence that the stoichiometry should be 2H + /2e -upon reduction during the O to R transition, rather than 1.4, with only 1 proton bound into the BNC, as found here (Table 1). Using photoexcited ruthium bispyridyl to deliver single electrons to the P. denitrificans oxidase BNC, electrometric measurements of wild type and Lys I-362 to Met mutants showed that one electrometric phase is inhibited in the mutants, suggesting that the first reduction is coupled to the proton uptake via the K channel (15,16). Multiple excitation accumulates the doubly reduced enzyme, which is associated with a slower electrometric phase, attributed to a second proton uptake (16).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the stoichiometry should be 2H + /2e -upon reduction during the O to R transition, rather than 1.4, with only 1 proton bound into the BNC, as found here (Table 1). Using photoexcited ruthium bispyridyl to deliver single electrons to the P. denitrificans oxidase BNC, electrometric measurements of wild type and Lys I-362 to Met mutants showed that one electrometric phase is inhibited in the mutants, suggesting that the first reduction is coupled to the proton uptake via the K channel (15,16). Multiple excitation accumulates the doubly reduced enzyme, which is associated with a slower electrometric phase, attributed to a second proton uptake (16).…”
Section: Discussionmentioning
confidence: 99%
“…Protonation State of Cross-linked Tyr-288 in Oxidized Form-Tyr-288 is located at the end of the K-channel (17)(18)(19)(20)(21)(22) and delivers one (or two) chemical protons to the heme-Cu B binuclear center (12,(25)(26)(27)(28). The presence of a peculiar C ⑀ -N ⑀ covalent bond between Tyr-288 and His-284 (19 -21, 43), one of three histidine ligands of Cu B , lowers the pK a of the phenol moiety (44 -46).…”
Section: Redox-induced Protein Structural Changes In Terminalmentioning
confidence: 99%
“…Upon two-electron reduction of the enzyme, two chemical protons are taken up from the cytoplasm to compensate for an increased negative charge at the binuclear center (12,33), and at least the first proton is delivered to the binuclear center by Tyr-288 at the end of the K-channel (27). If deprotonated at the oxidized (O) state (20), Tyr-288 serves as one of proton acceptors (26).…”
mentioning
confidence: 99%
See 2 more Smart Citations